Dinâmica populacional e produção secundária de Donax Hanleyanus (Philippi 1842) (Bivalvia, Donacidae) em uma praia exposta refletiva no litoral Sudeste do Brasil - ANJOS, Denys Willians Costa dos (2018)
The bivalve Donaxhanleyanus plays an important role in the trophic chain as suspension-feeders body, often presenting high production and acting as a key link between primary production and higher trophic levels organisms. This study evaluated the population dynamics and secondary production of D. hanleyanus on the exposed beach Vermelha do Norte, Ubatuba, Sao Paulo coast. This study aims to evaluate also the variation of the production of bivalve depending on the temperature and the morphodynamic state of the beaches using the data obtained in the Vermelha do Norte beach and available in the literature. Monthly samples were collected from July 2012 to June 2013 at the Vermelha beach along five transects perpendicular to the waterline in the intertidal zone. Sampling units were obtained every 3 meters along each transect, using a rectangular delimiter (0.50m x 0.40m). In the laboratory, the individuals were measured and divided into size classes, and ash free dry weight (AFDW) was calculated. The growth parameters and mortality rate of the population of D. hanleyanus in the Vermelha beach were obtained using the FISAT program. The secondary production and P/B of the population were estimated by the method of the specific growth rate in mass and mass-to-length relationship. To assess possible large-scale patterns of secondary production and P/B of D. hanleyanus, a thorough search of the literature was performed and based on the extracted data, estimates of production and P / B were related to temperature and some physical parameters (grain size and slope) of the beaches studied using simple relationships. It was observed a stratified distribution of D. hanleyanus in the Vermelha beach, with larger individuals occurring mainly in the turbulent swash zone, while smaller individuals occupy an area just above, as a result of different tolerances to abiotic factors. The low abundance of recruits probably was due to the beach steep reflectivity. The similarity of mortality D. hanleyanus in the Vermelha beach with the estimated for this bivalve in beach Restinga da Marambaia, located in Rio de Janeiro state, was unexpected considering that this is intermediate/dissipative and milder conditions than the reflective Vermelha do Norte beach. This may be due to interspecific competition between suspension-feeders D. hanleyanus and Emerita brasiliensis in Restinga, leading to increased mortality of bivalves in the latter beach. A smaller P/B value in Vermelha beach (1.25 yr-1) in relation to Restinga da Marambaia beach, reflects the lower proportion of recruits in the former beach. In a macroescale, the negative relationship between P/B of D. hanleyanuspopulations with the grain size and slope of the studied beaches show that in most dissipative conditions the turnover rate of this bivalve increases.